The persistence of secondary forests on colonist farms in the Brazilian Amazon - Smith, J.; Ferreira, S.; Kop, P. van de; Ferreira, C.A.P.; Sabogal, C. (2003)
While slash-and burn farmers convert forest to agriculture, they also regenerate significant areas of secondary fallow forests on their farms. Under what conditions does secondary forest cover persist on slash-and-burn farms?. Survey data from Para, Brazil show that secondary forests accupy 20% of farm area even after a century of settlement. In addition to restoring soil fertility, secondary forest contribute over 20% of farmers' income through products such as charcoal, fruit, game animals and firewood for on-farm processing. Econometric analysis shows that slow rates of population growth and increases in agricultural incomes through on-fram processing of agricultural products enable farmers to maintain long fallows and result in diversified systems compatible with secondary forest cover in the study area. On the other hand, declining agricultural productivity, subsidized credit, declines in the growth rate of secondary forests and policies favoring speculative land acquisition threaten secondary forest persistence. In older settlement areas, secondary forests are often the only forest resource available to the rural poor. Fallow areas should therefore be managed not only for agricultural productivity, but also for conserving forest resources.